1975
DOI: 10.1016/0043-1354(75)90125-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of trace metal species and measurement of trace metal stability constants by electrochemical techniques

Abstract: Differential pulse polarography and differential pulse anodic stripping voltammetry were used to determine copper, lead, cadmium and zinc complexes of relevance to environmental conditions. The dependency of peak current on pH and alkalinity was interpreted in terms of the variation in the metal species present. Stability constants of copper and lead complexes with carbonate were determined from the magnitude of the shift of peak potential using the method of Lingane. Inclusion of the transfer coefficient, cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(30 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…PbCO 3 (aq) and 6.1 and 5.7 for CuCO 3 (aq) [75EAa]. The absence of corrections for complexation of Pb 2+ and Cu 2+ by NO 3 -creates some ambiguity in both comparisons.…”
Section: Formation Of Pbco 3 (Aq)mentioning
confidence: 99%
“…PbCO 3 (aq) and 6.1 and 5.7 for CuCO 3 (aq) [75EAa]. The absence of corrections for complexation of Pb 2+ and Cu 2+ by NO 3 -creates some ambiguity in both comparisons.…”
Section: Formation Of Pbco 3 (Aq)mentioning
confidence: 99%
“…A value of 0.6 has been observed in other studies (6, lo), and a value of 1.0 would be expected if the mode of coordination by fulvic acid is similar to that exhibited by salicylic acid where one donor is a carboxyl oxygen and the other is a phenolic oxygen. It is presumed that the pK,'s of the phenolic oxygens will be greater than 8 and thus hydrogen ion dependence should approach unity. This interpretation assumes that the mode of complexation in each fulvic acid molecule is similar and thus can be quantitatively compared to precisely defined complexing agents.…”
Section: C6lmentioning
confidence: 99%
“…Anodic stripping voltammetry (5,6), differential pulse polarography (7,8), and ion selective electrodes (9, lo), have also been utilized to determine the degree of trace metal complexation in a variety of waters.…”
mentioning
confidence: 99%
“…There are several techniques for investigating the metal ion distribution in solution: anodic stripping voltammetry (ASV) (15)(16)(17), ion selective electrodes (18,19), and dialysis or ultrafiltration (20,21). Guy and Chakrabarti (22) have compared ASV and size separation procedures and concluded that, since the adsorption of organic substances onto the hanging mercury drop electrode makes the interpretation of stripping voltammograms difficult, the size separation procedures were more convenient.…”
Section: Introductionmentioning
confidence: 99%